THE IMPACT OF THE SOUTH AFRICAN LAW OF SUCCESSION AND ADMINISTRATION OF ESTATES ON SOUTH AFRICAN MUSLIMS - Abduroaf, Muneer (Jurnal Syariah, 2019)
Muslims have been living in South Africa for over 300 years. There are currently over 750 000 Muslims living in South Africa. These Muslims constitute a minority religious group in a non-Muslim country. There has (to date) been no legislation enacted by the South African parliament that gives effect to Islamic law provisions. This paper analyses the South African law of succession and administration of estates and looks at how it applies to the estates of deceased Muslims who lived in South Africa prior to dying. It looks at the possibility of using existing South African law provisions in order to apply the Islamic law of succession within the South African context. It concludes with an overall analysis and a recommendation.